The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18573/jomec.166
|View full text |Cite
|
Sign up to set email alerts
|

Do emotions fit the frame? A critical appraisal of visual framing research approaches

Abstract: With the rise of a visibly more emotional public sphere, this article asks if visual framing approaches can be enriched by the integration of emotive elements. Focusing on television news, I ask in what way emotions manifest within audio-visual material, and how these representations of emotions and emotive elements can be analyzed using visual framing analysis. This understanding is grounded in two recent turns: the turn to the visual and to the affective. Both turns provide the background for current framing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…In general, emotion classification can be divided into two classes: primary emotions such as joy, sadness, anger, fear disgust, and surprise, and secondary emotions, which evoke a mental image that correlates to memory or primary emotion. In psychology, Tomkins and Ekman connected the concept of emotions with universal face expressions, such as anger, sadness, or joy [43]. Nevertheless, this popular approach received criticism from scholars, such as Feldman Barrett [44], who emphasised the socio-cultural constructedness of emotions, pointing to the link between learning, emotion vocabulary, and emotion awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, emotion classification can be divided into two classes: primary emotions such as joy, sadness, anger, fear disgust, and surprise, and secondary emotions, which evoke a mental image that correlates to memory or primary emotion. In psychology, Tomkins and Ekman connected the concept of emotions with universal face expressions, such as anger, sadness, or joy [43]. Nevertheless, this popular approach received criticism from scholars, such as Feldman Barrett [44], who emphasised the socio-cultural constructedness of emotions, pointing to the link between learning, emotion vocabulary, and emotion awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that a more reliable and quick method of changing the public opinion is to change the emotional meaning and attitude to a particular problem, which is the most effective and quickest way to give a news story more prominence, draw the audience's attention to it and manipulate public opinion [7, p. 129]. Following the views of Antje Glück, who considered mediated emotions as a means and base of social communication [43], we define them as a set of conscious and unconscious emotional reactions of subjects or objects of reality to social and political events discussed in the media. Mediated emotions are mainly used with the purpose of public opinion manipulation, which occurs when a manipulative person (the journalist) seeks power over someone else (the reader) and employs dishonest or exploitive strategies to gain it.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Aristotle highlights the importance of an argument's emotional aspect and overcomes the dualism of rationality and emotionality in argumentation. This approach to the role of emotions in argumentation is reflected in modern media studies, which consider emotions as a means of both persuasion and manipulation that journalists deploy in news production (Glück 2018). Thus, these fundamental appeals to 'logos', 'pathos' and 'ethos' can be viewed not only as a way to persuade the audience but also as a way to manipulate public opinion, depending on the author's intentions.…”
Section: An Overview Of Fallacy Studiesmentioning
confidence: 99%
“…-the definition of visual framing, which still offers a ground for debate (Brantner, Geise & Lobinger, 2013;Bock, 2020); -the question of generic frames used in textual analysis and whether they are suitable for visual inquiry as well (Coleman, 2010); -the analysis of the moving image (Glück, 2018); -the methodological tools that adequately conceptualise the role of visuals as framing devices (Rodriguez & Dimitrova, 2011;Brantner, Geise & Lobinger, 2013;Geise & Baden, 2015); -the negligence of the unique properties of visual communication in favour of literal descriptions (Bock, 2020). Some of the above questions have been included in academic work on visual framing, however, they have not been adequately theorised.…”
Section: Visual Framingmentioning
confidence: 99%
“…The proposed approach focuses on the issuer's side, not the decoding of the images by recipients, the process of which is generally based on mentally stored ideas (Entman, 1993). Although the dissertation focuses on media frames, it must be noted that the extent of their influence can only be attested when combined with audience frames (Glück, 2018). Meaning associations do not only arise from news frames, but the audience also interprets them based on their existing knowledge and life experiences (Pan & Kosicki, 1993).…”
Section: Limitations Of the Approachmentioning
confidence: 99%